2017
DOI: 10.2514/1.j055598
|View full text |Cite
|
Sign up to set email alerts
|

Acoustics in a Two-Deck Viscothermal Boundary Layer over an Impedance Surface

Abstract: The acoustics of a mean flow boundary layer over an impedance surface or acoustic lining are considered. By considering a thick mean flow boundary layer (possibly due to turbulence), the boundary layer structure is separated asymptotically into two decks, with a thin weakly viscous mean flow boundary layer and an even thinner strongly viscous acoustic sublayer, without requiring a high-frequency. Using this, analytic solutions are found for the acoustic modes in a cylindrical lined duct. The mode shapes in eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…However, Renou and Auregan [13] demonstrated that to correlate mathematical and numerical results with the results of experiments, the effect of viscosity within the mean flow boundary layer must be included, and Khamis and Brambley [14,15] demonstrated that the effects of viscosity on the acoustics are of a comparable magnitude to the effects of shear, and thus both should be taken into account. Viscosity within the mean flow boundary layer was investigated by Aurégan, Starobinski, and Pagneux [7] for thin low-velocity mean flow boundary layers, and by Brambley [2] for thin mean flow boundary layers of arbitrary subsonic velocity, while investigations taking into account both shear and viscosity within the mean flow boundary layer have recently been performed by Khamis and Brambley [16,17]. This approach agrees most closely with results from solving the linearised Navier Stokes equations (LNSE) for the entire duct.…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…However, Renou and Auregan [13] demonstrated that to correlate mathematical and numerical results with the results of experiments, the effect of viscosity within the mean flow boundary layer must be included, and Khamis and Brambley [14,15] demonstrated that the effects of viscosity on the acoustics are of a comparable magnitude to the effects of shear, and thus both should be taken into account. Viscosity within the mean flow boundary layer was investigated by Aurégan, Starobinski, and Pagneux [7] for thin low-velocity mean flow boundary layers, and by Brambley [2] for thin mean flow boundary layers of arbitrary subsonic velocity, while investigations taking into account both shear and viscosity within the mean flow boundary layer have recently been performed by Khamis and Brambley [16,17]. This approach agrees most closely with results from solving the linearised Navier Stokes equations (LNSE) for the entire duct.…”
Section: Introductionmentioning
confidence: 53%
“…While asymptotic approximate solutions to equations (19,25,37) are possible [see, e.g. 2,17], here these equations are solved numerically using 4th order finite differences. The resulting 3N × 3N banded matrix system of equations is solved using the LAPACK_ZGBSV routine.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This shear stress is apparently due to the interaction between turbulent flow and the rough wall which is the interface of the acoustic treatment. Further attempts were made to account for shear stress in terms of viscous stress [9,10] or in term of additional force acting on the walls of a cavity [11]. A modified boundary condition was derived that introduces a coefficient β v that characterizes the transfer, by the normal fluctuating displacement, of axial momentum from the steady flow into the lined wall [9].…”
Section: Introductionmentioning
confidence: 99%